PENGEMBANGAN PERANGKAT PEMBELAJARAN TERPADU BERBASIS KEARIFAN LOKAL UNTUK KELAS III SEKOLAH DASAR DI KABUPATEN MADIUN - Dewi Tryanasari; Elly’s Mersina Mursidik; Edy Riyanto (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
This research is attempted to: (1) describe the steps of the development of local-wisdom-based integrated teaching media; (2) describe the quality of the local-wisdom-based teaching media; (3) describe the implementation of local-wisdom-based teaching media; and (4) describe the impacts of the implementation of local-wisdom-based teaching media. The method of the research is Dick and Carey’s model of Research and Development, which frames the development of teaching instruments. The objects of the research are the developed teaching instruments, and the subjects are 10 students of Balerejo II and 30 students of Balerejo IV. The data are analyzed descriptively by using observation record for the teaching events, and appraisal technique for the teaching instruments. The results of the analysis show that: (1) the teaching instruments can be well-developed being measured by the Dick and Carey’s model, which are scored as: 4.22 for Lesson Plan, 4.5 for Media, 4.14 for Teacher’s Guide, 4.26 for Book, and 3.96 Student Work Sheets; (2) the quality of the local-wisdom media is good; (3) the implementation of the model is good, by 89.75% of the application of lesson plan in the fisrt meeting and 91.01% in the second meeting. Students’ response is good, by 40.6 (agree) and 41.2 (very much agree). Teacher’s activities are good in response to the suggested activities of the lesson plan. Students’ activities are good with 99.41% of the activities are relevant to lesson plan, and the average achievement raise significantly. (4) Supporting factors cope with students’ experience in learning amusingly without disturbing contact to their mates. Some disadvantagous factors can be resolved by teacher’s improvisations. Key words:   Teaching Media Development, Integrated Teaching and Learning